2003
DOI: 10.1095/biolreprod.102.012369
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Capacity of Ferret Embryos by Nuclear Transfer Using G0/G1-Phase Fetal Fibroblasts1

Abstract: With the ultimate goal of establishing experimental protocols necessary for cloning ferrets, the present study has established parameters for the reconstruction of ferret embryos by nuclear transfer (NT) using G0/G1-phase donor fetal fibroblasts. Cumulus-oocyte complexes were harvested from superovulated ferrets and cultured in maturation medium for 24 h. Matured oocytes were then enucleated and injected with the fibroblast nuclei derived from 14-16-h serum-starved cells. Reconstructed embryos were then activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…3 The number of cleaved embryos or blastocysts was divided by the number of fused embryos. nuclear transfer recipient [12,13], relatively little information is available regarding the fusion of enucleated oocytes with donor cells. SLO is known to form pores in the plasma membranes of mammalian cells and has been used to deliver proteins into T-cells through those pores [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…3 The number of cleaved embryos or blastocysts was divided by the number of fused embryos. nuclear transfer recipient [12,13], relatively little information is available regarding the fusion of enucleated oocytes with donor cells. SLO is known to form pores in the plasma membranes of mammalian cells and has been used to deliver proteins into T-cells through those pores [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…It is the color pattern requested by most researchers, in contrast with the many coat color variations that abound in the pet industry. One research study, however, reported the use of albino ferrets as pseudopregnant recipients of embryos from cinnamon-colored parents (Li et al 2003).…”
Section: Research-related Ferret Selection Criteria and Biologymentioning
confidence: 99%
“…Over the past few years, several of the critical steps required for NT cloning in the ferret have been established [33-35]. This review will focus on progress in the various steps highlighted in Figure 2.…”
Section: Strategy and Progress In Cloning A Cf Ferretmentioning
confidence: 99%
“…Progress in each of the boxed methodologies will be discussed in detail in subsequent sections [33-35]. Italicized labels indicate descriptive markings, not methodological steps per se.…”
Section: Strategy and Progress In Cloning A Cf Ferretmentioning
confidence: 99%